Gender differences in health and health care utilisation in various ethnic groups in the Netherlands: a cross-sectional study - Devillé Walter L; Gerritsen Annette AM (BMC, 2009)
Abstract Background To determine gender differences in health and health care utilisation within and between various ethnic groups in the Netherlands. Methods Data from the second Dutch National Survey of General Practice (2000-2002) were used. A total of 7,789 persons from the indigenous population and 1,512 persons from the four largest migrant groups in the Netherlands - Morocco, Netherlands Antilles, Turkey and Surinam - aged 18 years and older were interviewed. Self-reported health outcomes studied were general health status and the presence of acute (past 14 days) and chronic conditions (past 12 months). And self-reported utilisation of the following health care services was analysed: having contacted a general practitioner (past 2 months), a medical specialist, physiotherapist or ambulatory mental health service (past 12 months), hospitalisation (past 12 months) and use of medication (past 14 days). Gender differences in these outcomes were examined within and between the ethnic groups, using logistic regression analyses. Results In general, women showed poorer health than men; the largest differences were found for the Turkish respondents, followed by Moroccans, and Surinamese. Furthermore, women from Morocco and the Netherlands Antilles more often contacted a general practitioner than men from these countries. Women from Turkey were more hospitalised than Turkish men. Women from Morocco more often contacted ambulatory mental health care than men from this country, and women with an indigenous background more often used over the counter medication than men with an indigenous background. Conclusion In general the self-reported health of women is worse compared to that of men, although the size of the gender differences may vary according to the particular health outcome and among the ethnic groups. This information might be helpful to develop policy to improve the health status of specific groups according to gender and ethnicity. In addition, in some ethnic groups, and for some types of health care services, the use by women is higher compared to that by men. More research is needed to explain these differences.